2015
DOI: 10.1136/bmjopen-2014-007266
|View full text |Cite
|
Sign up to set email alerts
|

Industrial hygiene, occupational safety and respiratory symptoms in the Pakistani cotton industry

Abstract: ObjectivesIn the cotton industry of Pakistan, 15 million people are employed and exposed to cotton dust, toxic chemicals, noise and physical hazards. The aim of this study was to determine the prevalence of health symptoms, particularly respiratory symptoms, and to measure cotton dust and endotoxin levels in different textile factories of Faisalabad, Pakistan.MethodsA cross-sectional investigation was performed in a representative sample of 47 cotton factories in the Faisalabad region in Punjab, Pakistan. Resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 27 publications
1
20
0
2
Order By: Relevance
“…Periodical medical check-ups, use of personal protective measures (eg, wearing masks) and proper ventilation and suction at workplaces are recommended,32 33 39 in order to reduce the harmful effects on respiratory health.…”
Section: Discussionmentioning
confidence: 99%
“…Periodical medical check-ups, use of personal protective measures (eg, wearing masks) and proper ventilation and suction at workplaces are recommended,32 33 39 in order to reduce the harmful effects on respiratory health.…”
Section: Discussionmentioning
confidence: 99%
“…The textile department workers had higher prevalence than the other workers for many diseases; for instance, respiratory diseases. Several other studies have also showed high prevalence of respiratory problems among the textile department workers (7,16). An exposure assessment study by (19) has measured higher dust exposure level among the textile production workers and the garment department workers in Ethiopia than the recommended threshold limit value in the ACGIH (26).…”
Section: Work-related Factorsmentioning
confidence: 99%
“…Since early 1900, the main research regarding work and health in the textile and garment industry has been focused on the respiratory disease, byssinosis (4). Several studies have indicated that processing raw cotton to clothing generates inhalable dust and endotoxin that might cause respiratory problem (5)(6)(7). However, the work processes in textile and garment production expose workers not only to dust but also to other different hazards (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Occupational hygiene and industrial hygiene includes within their ambit, multifaceted coverage of workers’ health, and are the subject of current research. [ 7 ] Information hygiene is another newly developed field of scientific study. [ 8 ]…”
Section: B Eyond C Ommunicable mentioning
confidence: 99%